Pemetaan Publikasi tentang Pendidikan Seksual Menggunakan VOSviewer - Nabilla Salsabil Damayanti Zahraa; Imam Yuadi (Politeknik Negeri Jember, 2022)
Sex education provides knowledge about sex and reproduction, including the reproductive organs which are accompanied by the cultivation of ethics for an individual can use the reproductive organ as well as possible. Unfortunately, sex education has become a polemic in society, especially in Indonesia. Sex education is still defined as something taboo. Sex education is a preventative the increase of cases that are not far from “sex”. This article aim’s to find out the growth and mapping of sex education publications, including the trend which is not only in Indonesia but also in other countries. In the search strategy, we applied the keyword “sex education” which is often used from 2019 to 2021 that are stored on Scopus. This article is based on a bibliometric analysis of a sex education publication using a computer program called VOSviewer with a 1.6.17 version for the Windows operating system. This article uses data from a collection of sex education publications from 2019 to 2021 which were taken from Scopus and exported into RIS and CSV formats. Through this analysis, the writer knows that the sex education publication from 2019 to 2021 that are stored on Scopus has increased significantly. The author who wrote the most sex education publication from 2019 to 2021 that is stored on Scopus is Bennett D.A. with 19 publications. The country which has the most sex education publication from 2019 to 2021 that are stored on Scopus is the United States with 700 publications. The main target of this research is the mapping of science on